The Effect of Using Noni Leaf Flour in Basal Diet on Intake and Digestibility Dry Organic and Organic Maters in Pigs - Dalle, Nautus Stivano; Nguru, David Agustinus; Nabut, Asael Ebson; Tukan, Hendrikus Demon; Nugraha, Elisabeth Yulia (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The purpose of this study was to study the effect of using leaf in basal rations on dry matter consumption and organic matter digestibility on landrace grade pigs. The material used in this study were 12 starter pigs for landrace breeds at the age of 1-2 months, variations in body weight from 10,5 kg - 18,5 kg on avege 16,7 kg and coefficient of variation 18,76 %. The design used was a randomized block design consisting of 4 treatments and 3 replications. The treatment tried is R0 100 % basal rations without noni leat flour (NLF), R1: 98 % basal ration + 2 % NLF, R2: 96 % basal rations + 4% NLF, R3: 94 % basal rations + 6 % NLF. The measured variable is dry matter intake, organic matter the results of variance showed that the use noni leaf flour had no significant effect (P>0,05) on the consumption and digestibility of dry materials and organic materials of Landrace pig breeding. The conclusion of this study is that the use of noni leaves 2,4,6 % in basal ration provides relatively similar benefits to dry matter consumption, organic matter digestibility and digestibility and digestibility organic matter in pig livestock.